PENGARUH EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA PADA SISWA KELAS XII DI SMK NEGERI 1 SURABAYA - WULANDARI, SUCI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Self efficacy refers on belief to ability which had by individual for actuated motivation, cognitive ability and action which needed for keep abreast of situation. So, self efficacy is an importing role to play in determine of success human in a specific task or a specific job as entrepreneurship. The students in Vocational School 1 Surabaya had very high of self efficacy to entrepreneurship. But, the student still have afraid and have doubt about entrepreneurship. This research is using quantitative approach with take a sample as many as 76 students. The research method is using a simple linier regression with use program SPSS 16.0 for windows. Whereas, the hypothesis testing using t-test showed that self efficacy partially has significant influence to interest entrepreneurship. Key Words:Self Efficacy, interst entrepreneurship